THE EFFECT OF PROFITABILITY, INDEPENDENT COMMISSIONERS, AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON TAX AVOIDANCE - Iklima, Ayu; Ayem, Sri (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to examine the effect of Profitability, Independent Commissioner, and Corporate Social Responsibility (CSR) on Tax Avoidance. The data used in the study is secondary data, the sampling technique is the purposive sampling method with data sources from financial statement data of banking companies listed on the IDX 2017-2019 obtained from the internet (www.IDX.co.id) as many as 45 companies consists of 135 samples. The test of this study used a classic assumption test consisting of (normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test) and multiple regression analysis hypothesis testing consisting of (determination coefficient test (R2), simultaneous test (F test), and partial test t-test). Based on the results of the regression test, it shows that the effect of Profitability, Independent Commissioner, and Corporate Social Responsibility (CSR) has a positive effect on tax avoidance.